(untitled) (The Review of Diabetic Studies, 2025)
Emergency Medical Services (EMS) represent a critical link between the scene of an emergency and definitive hospital care, with paramedics playing a central role in delivering rapid, life-saving interventions. Pre-hospital interventions—ranging from advanced airway management and cardiopulmonary resuscitation to trauma stabilization and medication administration—are key determinants of survival and long-term outcomes. This review explores the impact of paramedic-led pre-hospital interventions on patient care, highlighting their contribution to reducing mortality, improving neurological recovery, and enhancing system efficiency. Evidence from recent studies underscores the effectiveness of paramedic interventions in conditions such as cardiac arrest, road traffic accidents, and acute medical emergencies, where early treatment significantly influences prognosis. Moreover, technological innovations such as telemedicine and point-of-care diagnostics are reshaping paramedic practice, enabling more accurate assessments and informed clinical decisions before hospital arrival. Despite these advancements, challenges remain, including disparities in training standards, limited resources in low- and middle-income countries, and varying legal frameworks governing scope of practice. By synthesizing current evidence, this review emphasizes the critical role of paramedics in improving patient outcomes, while underscoring the need for continued research, policy support, and investment in EMS infrastructure.